Gender Differences in Using Social Media in Language and Literature Teaching in Multicultural Context - CASIPIT, DAISY; CARA-ALAMANI, EVELITA; RAVAGO, JOAN; REYES, MERCEDITA; PAGAY, JENALYN; TAGASA, GINA (International Journal of Language and Literary Studies, 2022)
This paper presents a systematic review of the literature on gender differences using social media to teach language and literature in multicultural contexts published in EBSCO, ERIC, Google Scholar, and SAGE databases. The articles reviewed were put on a grid to facilitate thematizing the data needed to answer the objectives. The findings of the study revealed a gender divide as regards the use of social media, such as females tend to utilize available social media platforms more than males in the case of teachers and show more positive responses to social media use in the classroom. Generally, social media proved to hone the language skills (e.g., writing, reading) and critical thinking skills of the learners, improve communicative competence, develop vocabulary, promote language learning inside and outside the classroom, increase individual and group motivation to learn and succeed, engage students in critical, creative, and collaborative participation in transforming the textual world into a dynamic online community, create meaningful connections for authentic language situations, and support various types of learning styles. Finally, the paper suggests further research on gender differences in social media usage in gender-sensitive teaching in language and literature.